Walter White's Moral Transformation in the Breaking Bad Series: A Semiotic Analysis Based on Friedrich Nietzsche's Six Tasks of the Camel Spirit - Dimas Anargya Bhagaskara; Maylanny Christin (Green Publisher Indonesia, 2025)
This study examines the moral transformation of Walter White in the Breaking Bad series through a semiotic analysis based on Friedrich Nietzsche's concept of the